ESTIMASI PARAMETER SISTEM DENGAN MENGGUNAKAN MASUKAN ACAK - Wahjudi, Rudy S; Pudjiastuti, Christina Eni (Jurnal Teknik Elektro, 2003)
The design of feedback control system still using pole placement until now. Therefore theinformation of system parameters was required. One of the way to obtained information ofsystem parameters by system parameter estimator. This estimation process is required thecolection of input-output data. Input-output data can obtained from natural system(unspecify generated). This paper present estimator design using random input (not stepfunction). Estimation method using âLeast Squareâ. The resulted of simulator design wassimulated. From this simulation of parameter estimator is good result indicated.Keywords: feedback, control system, estimator, Least Square.